Global classroom: Exploring tree with BINUS University - Yuhani, Yusof (Pusat Sains Matematik UMPSA, 2024)
As a global classroom initiative 2024, Centre for Mathematical Sciences (CMS) has organized a basic global classroom session with Bina Nusantara University (BINUS University) for DUM1433- Discrete Structure & Applications course on 15th May 2024. An hour session is conducted at 8.45 am connecting 60 DRC students from section 01P with renowned speaker Mrs. Viska Noviantri. The session, titled “Tree and Its Applications” delved into the properties of trees and their applications, including binary search tree, chemical representation of molecules, mathematical expressions, and probability statistics. As the moderator and instructor of the course from UMPSA, Assoc. Prof. Dr. Yuhani highlights that this session not only enriched the students’ academic experience but also paved the way for future research collaborations between two universities in fostering global academic connections.